Association of Type 1 Diabetes and Hypoglycemic and Hyperglycemic Events and Risk of Dementia - Whitmer, Rachel A. (Neurology, 2021)
OBJECTIVE: To determine whether severe hypoglycemic and hyperglycemic events are associated with longitudinal dementia risk in older adults with type 1 diabetes. METHODS: A longitudinal cohort study followed up 2,821 members of an integrated health care delivery system with type 1 diabetes from 1997 to 2015. Hypoglycemic and hyperglycemic events requiring emergency room or hospitalization were abstracted from medical records beginning January 1, 1996, through cohort entry. Participants were followed up for dementia diagnosis through September 30, 2015. Dementia risk was examined with Cox proportional hazard models adjusted for age (as time scale), sex, race/ethnicity, hemoglobin A1c, depression, stroke, and nephropathy. RESULTS: Among 2,821 older adults (mean age 56 years) with type 1 diabetes, 398 (14%) had a history of severe hypoglycemia, 335 (12%) had severe hyperglycemia, and 87 (3%) had both. Over a mean 6.9 years of follow-up, 153 individuals (5.4%) developed dementia. In fully adjusted models, individuals with hypoglycemic events had 66% greater risk of dementia than those without a hypoglycemic event (hazard ratio [HR] 1.66, 95% confidence interval [CI] 1.09, 2.53), while those with hyperglycemic events had >2 times the risk (HR 2.11, 95% CI 1.24, 3.59) than those without a hyperglycemic event. There was a 6-fold greater risk of dementia in individuals with both severe hypoglycemia and hyperglycemia vs those with neither (HR 6.20, 95% CI 3.02, 12.70). CONCLUSIONS: For older individuals with type 1 diabetes, severe hypoglycemic and hyperglycemic events are associated with increased future risk of dementia.